2019
DOI: 10.3390/ijms20020371
|View full text |Cite
|
Sign up to set email alerts
|

TRP Channels as Sensors of Chemically-Induced Changes in Cell Membrane Mechanical Properties

Abstract: Transient Receptor Potential ion channels (TRPs) have been described as polymodal sensors, being responsible for transducing a wide variety of stimuli, and being involved in sensory functions such as chemosensation, thermosensation, mechanosensation, and photosensation. Mechanical and chemical stresses exerted on the membrane can be transduced by specialized proteins into meaningful intracellular biochemical signaling, resulting in physiological changes. Of particular interest are compounds that can change the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 191 publications
(241 reference statements)
1
50
0
1
Order By: Relevance
“…Another interesting aspect on TRPA1 mechanosensation is that the effect of non-electrophilic TRPA1 ligands may be indirect by changing the lipid tension stress on TRPA1 within the cell membrane (17). For example, the ability of primary and secondary alcohols as well as different alkyl-substituted phenol derivatives including carvacrol to activate hTRPA1 increased with increasing lipophilicity (17). Our observation that carvacrol induced conformational changes of purified hTRPA1 in a bilayer-free environment indicates, however, a direct interaction with TRPA1 (9).…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting aspect on TRPA1 mechanosensation is that the effect of non-electrophilic TRPA1 ligands may be indirect by changing the lipid tension stress on TRPA1 within the cell membrane (17). For example, the ability of primary and secondary alcohols as well as different alkyl-substituted phenol derivatives including carvacrol to activate hTRPA1 increased with increasing lipophilicity (17). Our observation that carvacrol induced conformational changes of purified hTRPA1 in a bilayer-free environment indicates, however, a direct interaction with TRPA1 (9).…”
Section: Discussionmentioning
confidence: 99%
“…The authors identified by in silico investigation cholesterol recognition amino acid consensus motifs in the TM2 and TM4 segments, which had a role in the inhibition of chemical activation of mouse TRPA1 by cholesterol depletors [ 34 ]. Cholesterol might influence TRP channel function by direct interaction with ion channels [ 34 , 35 , 36 ]. Sphingomyelinase hydrolyzes SM to phosphocholine and ceramide [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanism underlying TRPV4 activation by LPS remains to be fully clarified. However, because of the widely reported mechanosensitivity of this channel (34-36), we hypothesize that it could be similar as that operating in TRPA1, i.e., via the detection of LPS-induced mechanical perturbations in the plasma membrane (27,(37)(38)(39).…”
Section: Discussionmentioning
confidence: 95%